Synthesis and Spectral Properties of Dioxouranium(VI) Complexes of N-isonicotinamidio-p-anisalaldimine and N-isonicotinamido-p-dimethylaminobenzalaldimine† - Singh, Lakshman; Pal Dhaka, Naresh; K. Manglik, Ajay (Asian Journal of Chemistry, 2010)
In the present work, the ligational behaviour of N-isonicotinamido- p-anisalaldimine (INH-ANSL) and N-isonicotinamido-p-dimethylaminobenzalaldimine (INH-PDAB) toward dioxouranium (VI) salts were studied. The isolated complexes have the general composition UO2X2·nL (X = Br–, I–, NCS–, NO–3) or CH3COO–, n = 2, X = ClO–4, n = 3 and L = INH-ANSL or INH-PDAB). All these complexes were characterized by infrared, conductance, magnetic moment, molecular weight data and elemental analyses. In these complexes both the ligands behave as neutral bidentate ligand coordinating through amido-oxygen and azomethinic-nitrogen atoms. The electrical conductance indicates that except UO2(ClO4)2 complexes all the complexes are non-electrolytes, while UO2(ClO4)2·3L are 1 : 2 electrolytes. The probable coordination number of U(VI) is either 8 or 10 depending on the nature of anions. Thermal properties of the complexes are also discussed.